2016
DOI: 10.1590/s0102-053620160000200009
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth response of subirrigated salvia 'Vista Red' to increasing water levels at two substrates

Abstract: Subirrigation applies water and nutrients to the bottom of pots without wetting leaves, improving water use and reducing disease spread compared to overhead irrigation systems. However, water levels applied within the benches are often higher than required to promote capillary action, applying more water than needed and wasting pumping energy. The present study was conducted to evaluate the effect of different water levels on plant growth of subirrigated salvia (Salvia splendens) 'Vista Red' in two substrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In contrast, Rouphael and Colla [29,30] suggested that subirrigation using the trough technique may provide higher or similar yield and fruit quality when compared with drip irrigation. Cases where lower water use efficiency was observed in ebb and flow systems have usually been attributed to using timers set to a predetermined schedule for long timeframes, without monitoring plant water requirements or substrate moisture levels, resulting in excess plant water uptake [31,32]. Some authors have shown that to overcome this, the use of soil moisture sensors or partial saturation of the substrate may control excess water consumption and allow ebb and flow to achieve a higher WUE and better plant growth [3,26,32].…”
Section: Capillary Irrigation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Rouphael and Colla [29,30] suggested that subirrigation using the trough technique may provide higher or similar yield and fruit quality when compared with drip irrigation. Cases where lower water use efficiency was observed in ebb and flow systems have usually been attributed to using timers set to a predetermined schedule for long timeframes, without monitoring plant water requirements or substrate moisture levels, resulting in excess plant water uptake [31,32]. Some authors have shown that to overcome this, the use of soil moisture sensors or partial saturation of the substrate may control excess water consumption and allow ebb and flow to achieve a higher WUE and better plant growth [3,26,32].…”
Section: Capillary Irrigation Systemsmentioning
confidence: 99%
“…One study showed that water and fertiliser use efficiency was improved by 20 to 30% through adopting a regime of holding water on the floor for a shorter duration (3 to 5 min) compared with longer duration (10 to 15 min), without affecting the plant nutrient composition or flower development rate [34]. Ferrarezi et al [31] observed that different water levels did not affect plant growth in an ebb and flow system, and hence, the application of water according to minimum plant requirements could minimise the nutrient solution pumping costs compared with in systems that apply higher water levels. Meanwhile, Montesano et al [35] found that precise control of substrate water status through tensiometer-based irrigation may offer the possibility to steer crop response by enhancing different crop performance components, namely, yield and fruit quality, in subirrigated tomato.…”
Section: Capillary Irrigation Systemsmentioning
confidence: 99%
“…For a review of the use of different sensors in irrigation control, see van . Subirrigation has been successfully automated using tensiometers (Montesano et al, 2010;Rouphael and Colla, 2009;Rouphael et al, 2006Rouphael et al, , 2008, lysimeters (Melo et al, 2013), and capacitance moisture sensors (Ferrarezi et al, 2013(Ferrarezi et al, , 2014(Ferrarezi et al, , 2015a(Ferrarezi et al, , 2015b. Electronic switches connected to tensiometers to begin and end irrigation events at -5 and -1 kPa substrate matric potential (high and low media tension values, respectively) in drip and trough-tray irrigated containers were tested in several studies (Rouphael et al, 2008;Rouphael and Colla, 2009).…”
Section: Sensor-based Subirrigation Controlmentioning
confidence: 99%
“…However, when relatively low fertilizer concentrations were used, subirrigation resulted in equal yields as open-cycle drip irrigation. Triggering irrigation based on specific substrate moisture levels cannot only reduce water use, it can also be used to control plant vigor, potentially reducing the need for plant growth retardant applications (Ferrarezi et al, 2015a(Ferrarezi et al, , 2015b. Inexpensive open-source microcontrollers can be used to build low-cost automated irrigation controllers (Ferrarezi et al, 2015c).…”
Section: Sensor-based Subirrigation Controlmentioning
confidence: 99%